Persepsi Siswa pada Bimbingan Konseling Kelas VIII di SMP Negeri 39 Semarang - Rizqishanty, Aqila Salma; Setianingsih, Eka Sari; Ajie, G. Rohastono (Melati Institute, 2024)
This study is motivated by some VIII grade students lack of understanding of the functions and benefits of counseling guidance at SMP Negeri 39 Semarang, it also affects the existence of a few VIII grade students who do individual counseling with counseling teachers. The purpose to be achieved in this study is to determine the factors that influence students' perceptions of Guidance and Counseling at SMP Negeri 39 Semarang. This type of research is qualitative research. The subjects used in the study were 5 students and 1 counseling teacher. The data in this study were obtained through interviews, observations, and documentation. Based on the data obtained from the research subjects, it shows that the factors that cause students there are 2 factors, namely internal factors and external factors. Suggestions that can be conveyed by researchers should BK teachers be able to find the right techniques or methods used in guidance and counseling so as to change students' perceptions of guidance and counseling for the better through services and guidance to students, both problematic students and students who are not problematic.